Muslim Women's Identity in the Modern Era: Navigating Sharia-Compliant Hijab and Contemporary Fashion Trends - Tebi Rahmadani (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study aims to examine how Muslim women's identities in the modern era are constructed through the use of sharia hijab and fashion trend hijab, two forms of expression that are often considered opposite but in fact coexist in social, cultural, and religious spaces. The hijab is not only seen as a religious obligation, but also as a symbol of identity, lifestyle, and part of the dynamics of globalization and fashion consumption. Theoretical framework: This research combines social identity theory that explains how groups form identity through symbols, Stuart Hall's theory of representation that highlights how meaning is produced through cultural practices, and ideas about modernity and consumerism that explain the shift of the hijab from a mere shari'a obligation to a lifestyle commodity. Literature review: shows that previous studies tend to separate the shari'i hijab as a religious expression and the fashion hijab as a modern expression, but it is still limited in analyzing the dialectics of both within the framework of contemporary Muslim women's identity. Methods: This study uses a qualitative method with literature studies and discourse analysis, with data sourced from academic articles, books, social media, advertising, and previous research, then analyzed thematically to understand how the meaning of hijab is negotiated. Results: The research shows that the shari'i hijab represents religious identity, piety, and moral commitment, while the fashion trend hijab emphasizes more aesthetic aspects, social status, and openness to popular culture; both interact to form a religious and modern Muslim woman's dual identity. Implications: The study includes the social aspect, where the hijab becomes an arena of plurality of expression; the cultural aspect, where the hijab becomes a symbol of negotiation between traditional and contemporary values; and the religious aspect, where the hijab is understood flexibly according to the context. Novelty: This research lies in a comparative analysis that juxtaposes the sharia hijab and the fashion trend hijab within the framework of modern Muslim women's identity, and offers an understanding that the hijab is not just a single symbol, but a dynamic and adaptive identity representation space.